2019
DOI: 10.1017/thg.2019.72
|View full text |Cite
|
Sign up to set email alerts
|

The Danish Twin Registry: An Updated Overview

Abstract: The Danish Twin Registry (DTR) was established in the 1950s, when twins born from 1870 to 1910 were ascertained, and has since been extended to include twins from birth cohorts until 2009. The DTR currently comprises of more than 175,000 twins from the 140 birth cohorts. This makes the DTR the oldest nationwide twin register and among the largest in the world. The combination of data from several surveys, including biological samples and repeated measurements on the same individuals, and data from Danish natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 64 publications
(69 reference statements)
0
56
0
Order By: Relevance
“…However, the genetic variation of the pattern was of almost the same magnitude in the youngest Class 1 and oldest Class 4, although there was more than 15 years difference in median age, indicating that age may not be the primary determinant of the total phenotypic variation. Although we used a population-based register for recruitment (Pedersen et al, 2019), the participants were twins, which could limit the generalizability of our findings to singletons. Nevertheless, several studies have found similar prevalences of type 2 diabetes and other diseases in twins and singletons (Christensen et al, 2001;Petersen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the genetic variation of the pattern was of almost the same magnitude in the youngest Class 1 and oldest Class 4, although there was more than 15 years difference in median age, indicating that age may not be the primary determinant of the total phenotypic variation. Although we used a population-based register for recruitment (Pedersen et al, 2019), the participants were twins, which could limit the generalizability of our findings to singletons. Nevertheless, several studies have found similar prevalences of type 2 diabetes and other diseases in twins and singletons (Christensen et al, 2001;Petersen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The GEMINAKAR cohort was initiated in 1997 as an observational, prospective twin cohort study of 756 complete twin-pairs, aged 18-67 years, recruited from the nationwide populationbased Danish Twin Registry during 1997-2000 as previously described (Pedersen et al, 2019;Schousboe et al, 2003). To be included in the GEMINAKAR cohort, both twins in a pair had to be willing to participate.…”
Section: Study Populationmentioning
confidence: 99%
“…The studied cohort of ninety-five individuals (Table 1) was recruited from the 2008-2011 survey of middle-aged twins of the Danish Twin Registry [28] based on sample availability and overlaps with the cohort of the earlier study [27]. Zygosity was determined by a questionnaire on the degree of similarity between twins in a pair [29] and only twin pairs of the same sex were included.…”
Section: Cohortmentioning
confidence: 99%
“…However, we have previously reported correlations of CD4+ and CD8+ T cell differentiation indices in CMV-seropositive monozygotic (MZ) but not in dizygotic (DZ) twin pairs [27], consistent with a strong genetic influence. Here, we studied the genetic impact on the "unconventional" γδ T cell compartment in comparison to the "classical" CD4+ and CD8+ T cells in a subsample of the same cohort [27] of middle-aged MZ and DZ twin pairs from the Danish Twin Registry [28]. Significantly greater similarity between MZ twins, who share all their genes, compared to DZ twins, sharing approximately half of their genes, implies the existence of a genetic influence on the investigated trait.…”
Section: Introductionmentioning
confidence: 99%
“…MADT was initiated in 1998 as a Danish nation-wide study of 4,314 twins randomly selected from the consecutive birth cohorts of 1931-1952. In 2008-2011 a follow-up study was performed on all eligible twin pairs originally enrolled (Pedersen et al, 2019). Zygosity was established by four questions regarding physical similarity, which correctly classified more than 95% of the pairs (Christiansen et al, 2003).…”
Section: Study Population and Phenotype Datamentioning
confidence: 99%